Morini, M. (2022). Theatre Translation: Theory and Practice. Bloomsbury Academic. http://doi.org/10.5040/9781350195653 (pp. 168) - Soleimanirad, Elmira (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
Book review